Zika Virus (ZIKV) Infection: Considerations for Assisted Reproductive Technology and Reproductive Health—A Narrative Review - Illoney Nindya Kamila; Fathiy Zakaria Aslama; Ichsan Abdillah Murtadlo; Pakpahan, Cennikon (Universitas Airlangga, 2025)
ABSTRACT Background : Zika virus (ZIKV) is a small, enveloped, single-stranded RNA virus belonging to the Flavivirus genus. It is primarily transmitted through mosquito bites, particularly from the Aedes aegypti species, and has been reported in 89 countries as of December 2021. Notably, ZIKV is the first arbovirus known to spread through sexual contact and can also be transmitted vertically from mother to fetus, raising significant reproductive health concerns due to its persistence in reproductive tissues and association with severe fetal abnormalities. As assisted reproductive technologies (ART) gain importance for family planning, ZIKV's implications extend beyond natural conception, affecting the safety of gametes and embryos used in ART. Reviews : The search method of this literature review was done in several databases such as Pubmed, Scopus, Cochrane, Web of Science, CINAHL, and Proquest using keywords (“Zika Virus”) AND (“Assisted Reproductive Technology”). The types of studies are in-vitro, in-vivo, pre-clinical, and clinical studies that assess the effect of Zika virus infection in reproductive health. We are also focusing on the study that discusses the concept of Zika virus infection, reproductive health, Assisted Reproductive Technologies, risk of ZIKV transmission in ART, and procedures including pre-counseling, risk assessment, and screening protocols in ART. The author was last searched on 5th December 2024. Summary : Zika virus (ZIKV) infection poses significant risks during assisted reproductive technology (ART) due to its potential for sexual transmission and prolonged presence in reproductive tissues, necessitating rigorous screening and management protocols to ensure reproductive health and safety Keywords : Zika virus, Assisted Reproductive Technology (ART), and Reproductive Health